The Effect of Gamma Irradiation on HDPE/HA Composite as Candidate Material Dental Implant - Pormauli Gultom; Sigit T. Wicaksono; Agung Purniawan; Sudirman Sudirman; Sulistiyoso Giat Sukaryo (IPTEK The Journal for Technology and Science, 2020)
Hydroxyapatite (HA) Ca10.P O4/6.OH/2 is the main component of calcium phosphate-based bone, which is most widely used in biomaterial applications because it has non-toxic and biocompatible properties. But if used alone, HA does not have excellent mechanical strength and is not resistant to pressure. High-Density Polyethylene (HDPE) is a high density of synthetic polymers, and hydroxyapatite (HA) is a vital bone component. Composites of them will make synthetic bones, with HDPE as matrix and HA as fillers. HDPE/HA composites with a composition variation of 0%, 5%, 10% HA were compacted and heated at 180°C for 90 minutes, and then irradiated at a dose of 60 kGy. The effect of adding HA composition and gamma irradiation was observed by hardness testing and characterized using XRD and FTIR. The results showed that the addition of HA increased the hardness of HDPE. From the XRD and FTIR analysis, there was no change in the composite phase after irradiation.